150 PROVE study 506: Perampanel as adjunctive therapy or monotherapy in real- world care of epilepsy patients. Issue 6 (27th May 2022) - Kuzniecky, Ruben; Wechsler, Robert T; Patten, Anna; Malhotra, Manoj
Abstract : Background: We report an analysis of PROVE Study 506 (NCT03208660 ) in epilepsy patients who received perampanel (adjunctive or monotherapy) during routine care. Methods: Data were from patients initiating perampanel after 01-Jan-2014 (cut-off: 15-Mar-2019). Retention rate (primary endpoint; patients remaining on perampanel at 3/6/12/18/24 months following initiation [Safety Analysis Set (SAS)]), dosing and safety were assessed. Patients received adjunctive perampanel (with concomitant anti-seizure medications [ASMs]) or perampanel monotherapy (primary=without con- comitant ASMs; secondary=conversion to monotherapy). Results: SAS included 1676 (98.4%) patients receiving adjunctive perampanel and 47 (2.8%) receiving monotherapy. Patients receiving adjunctive perampanel and perampanel monotherapy (primary, n=33/secondary, n=14) are in each relevant group. Most patients on adjunctive perampanel received 1–3 baseline ASMs (77.6%). Overall, 816 (47.9%) patients discontinued (monotherapy, n=23 [48.9%]); most commonly due to adverse event (overall, 22.8%; monotherapy, 14.9%) and inadequate therapeutic effect (overall, 13.2%; mono- therapy, 25.5%). Retention rates (24 months) were: 47.6% (adjunctive); 31.3% (primary monotherapy); 83.3% (secondary monotherapy). Mean (standard deviation) maximum perampanel doses (mg) were: adjunctive, 6.6 (3.2); monotherapy, 7.2 (2.7). Treatment-emergent adverse events occurred in 696 (adjunctive; 41.5%) and 17 (monotherapy; 36.2%) patients; dizziness was most common. Conclusion: Retention on perampanel (adjunctive/monotherapy) was favourable for ≤2 years, with similar safety between groups. Funding: Eisai Inc. manoj_malhotra@eisai.com